KANDUNGAN PUPUK ORGANIK CAIR BERBAHAN DASAR SERASAH TUMBUHAN API-API (Avicennia marina (Forsk.) Vierh.) DAN KETAPANG (Terminalia catappa Linn.) - Mukarlina Mukarlina; Riza Linda; Sartika Debora Br Ginting (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
Liquid organic fertilizer is one type of organic fertilizer that utilizes organic materials such as plant residues or animal waste that have been decomposed by microbiological activity and will produce nutrients. Sources of organic matter that can be used as liquid organic fertilizer is plant litter. This study aims to determine the content of liquid organic fertilizer based on api-api plant litter (Avicennia marina (Forsk.) Vierh.) and ketapang (Terminalia catappa Linn.). Liquid organic fertilizer in this study was carried out by chopping the litter into small pieces then given a solution of EM4 and granulated sugar and then stirred to make it homogeneous and put in a closed container for 14 days. This study uses descriptive analysis, which compares data from liquid organic fertilizer based on api-api litter contains nutrients with liquid organic fertilizer based on ketapang litter contains nutrients. The results show that liquid organic fertilizer based on api-api litter contains nutrients, namely 0.10% C-organic, N-total 0 .4%, NPK 0.11%, Calcium (Ca) 26.85% and Magnesium (Mg) 0.03%. Liquid organic fertilizer based on ketapang litter contains nutrients, namely C-organic 6.20%, N-total 0.19%, NPK 2.22%, Ca 35.83% and Mg 0.53%.